Founding Editorial – Forensics and TheScientificWorld - Walter Rowe (The Scientific World Journal)
At the beginning of a new millennium it seems a good idea to stop for a moment and take stock of the current state of forensic science. As a field of scientific research and scientific application, forensic science is a little more than a century old. Forensic science may be said to have begun in 1887 with the simultaneous publication of A. Conan Doyle’s A Study in Scarlet and Hans Gross’s Handbuch für Untersuchungsrichter. Conan Doyle’s novel introduced to the world the character of Sherlock Holmes, whose literary career would popularize the use of physical evidence in criminal investigations. Gross’s manual for examining magistrates suggests ways in which the expertise of chemists, biologists, geologists, and other natural scientists could contribute to investigations. Gross’s book was translated into a number of languages and went through various updated editions during the course of the century. The intervening century saw the development and application of fingerprinting, firearm and tool mark identification, forensic chemistry, forensic biology, forensic toxicology, forensic odontology, forensic pathology, and forensic engineering. Increasingly, the judicial systems of the industrial nations of the world have come to rely upon the expertise of scientists in a variety of disciplines. In most advanced countries, virtually all criminal prosecutions now involve the presentation of scientific testimony. This has had the beneficial effect of diminishing the reliance of courts on eyewitness testimony and defendant confessions.